Open custody for criminal youth hold back re-offending (Sociologisk Forskning, 2017)
In Sweden, youths who commit very serious offences are sentenced to youth custody. This article addresses issues relating to how these children experience being incarcerated, the significance of custodial openness for their everyday institutional lives, and how the experience of more open custodial forms during youth custody sentences is related to re-offending. The empirical data provide support for the significance of more open custodial forms as a means of both providing incarcerated youths with a less destructive environment and increasing the likelihood of more positive re-offending outcomes following their release.
Keywords: re-offending; youth custody; custodial openness